(untitled) (Plant Tissue Culture and Biotechnology, 2010)
RAPD assay was conducted for molecular genetic analysis of six wheat cultivars, such as, Kanchan, Sourav, Gourab, Shatabdi, Pavon and BAW-1006 to observe genetic variability and relatedness among these cultivars. Three out of 12 decamer random primers showed distinctly polymorphic bands when used to amplify genomic DNA. The primers yielded a total of 23 RAPD markers of which 14 were considered as polymorphic. The proportion of polymorphic loci and gene diversity (h) values were 34.78% and 0.153 for BAW-1006, 30.43% and 0.124 for Kanchan, 26.09% and 0.127 for Shatabdi, 26.09% and 0.127 for Pavon, 26.09% and 0.111 for Gourab, 21.74% and 0.098 for Sourav, respectively. The coefficient of gene differentiation (Gst) and gene flow (Nm) values across all the loci were 0.50 and 0.50, respectively indicating genetic divergence among populations. The UPGMA dendrogram based on Nei’s genetic distance, grouped six cultivars into two main clusters: Kanchan, Sourav, Gourab and Shatabdi in cluster I; Pavon and BAW-1006 in cluster II. The cluster I was further separated: Kanchan alone in sub-cluster I and Sourav, Gourab, Shatabdi in sub-cluster II; furthermore, Sourab and Gourab grouped together in sub-sub-cluster I of sub-cluster II with the lowest genetic distance of 0.035. Thus, RAPD offer a potentially simple, rapid and reliable method to evaluate genetic variation and relatedness among six wheat cultivars. Key words: RAPD, genetic diversity, polymorphic loci, wheat D.O.I. 10.3329/ptcb.v19i1.4915 Plant Tissue Cult. & Biotech. 19(1): 35-44, 2009 (June)